Propofol Ameliorates H9c2 Cells Apoptosis Induced by Oxygen Glucose Deprivation and Reperfusion Injury via Inhibiting High Levels of Mitochondrial Fusion and Fission - Zhao, Lidong; Zhuang, Jinqiang; Wang, Yihui; Zhou, Dandan; Zhao, Dandan; Zhu, Shun; Pu, Jinjun; Zhang, Hongyu; Yin, Ming; Zhao, Wenjuan; Wang, Zejian; Hong, Jiang (Frontiers in Pharmacology, 2019)
Abstract Background: Cardioprotective effect of propofol on ischemia-reperfusion injury (I/R injury) is partly due to suppressing apoptosis. Besides, mitochondrial dynamics are involved in apoptosis. Mitochondrial fusion and fission lead to mitochondrial morphological changes. However, whether suppressing apoptosis effect of propofol against ischemia-reperfusion injury in heart via regulating mitochondrial morphology remains unclear. Methods: H9c2 cells underwent oxygen glucose deprivation followed by reperfusion to simulate cardiomyocytes ischemia/reperfusion injury. Cell viability, apoptosis ratio and intracellular reactive oxygen species (ROS) were assessed respectively. Mitochondrial membrane dynamin family proteins, extracellular signal regulated kinase 1 and 2 (ERK1/2), phosphorylated extracellular signal regulated kinase 1 and 2 (p-ERK1/2) and proteins related to intrinsic apoptosis pathway were detected by western blotting. Mitochondrial morphology and the distribution of dynamin related protein 1 (Drp1) were observed by using laser confocal microscopy. Results: Propofol enhanced the survival of H9c2 cells, decreased ROS levels and inhibited apoptosis during oxygen glucose deprivation/ reperfusion (OGD/R) injury. Mitochondrial fission in H9c2 cells was inhibited by propofol during OGD injury. Propofol alleviated high levels of mitochondrial fusion and fission during OGD/R in H9c2 cells by regulating mitochondrial membrane remodelling dynamin family proteins. Propofol inhibited Drp1 colocalization with mitochondria in H9c2 cells during OGD/R injury. Moreover, Drp1 phosphorylation was inhibited by propofol through decreasing ERK activation during OGD/R injury. We found that propofol ameliorated H9c2 cells apoptosis during OGD/R via inhibiting mitochondrial cytochrome c release and caspase-9, caspase-6, caspase-7 and caspase-3 activation. Conclusion: Propofol suppresses H9c2 cells apoptosis during OGD/R injury via inhibiting intrinsic apoptosis pathway, which may be partly due to reducing high levels of mitochondrial fusion and fission induced by OGD/R injury.